PENGARUH PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN GAWAT DARURAT BADAN LAYANAN UMUM DAERAH RSUD BALANGAN PROVINSI KALIMANTAN SELATAN - Meiliana, Riesa; Kusbandrijo, Bambang; Rochim, Achluddin Ibnu (SENTRI: Jurnal Riset Ilmiah, 2024)
Health services are one of the many important needs for the community and are one of the basic rights of the community whose provision must be provided by the government as mandated in the 1945 Constitution Article 28 paragraph (1) "Everyone has the right to live in physical and mental prosperity. mentally, have a place to live, and have a good and healthy living environment and are entitled to health services” and Article 34 paragraph (3) “The state is responsible for the provision of proper public service facilities”. The purpose of this study was to determine the effect of service, trust, product quality and service quality on patient satisfaction in the emergency department of the Balangan Regional Public Service Agency. This study uses a quantitative approach. The number of samples used in this study were 93 samples of patients.Based on the results obtained, it is stated that the trust variable has a positive and significant effect on patient satisfaction in the emergency department of the Regional Public Service Agency of Balangan Hospital. (2) The service quality variable has a positive and significant effect on patient satisfaction in the emergency department of the Regional Public Service Agency of Balangan Hospital. (3) The variables of trust and service quality have a positive and significant effect on patient satisfaction in the emergency department of the Regional Public Service Agency of Balangan Hospital